Experimental and Numerical Investigation of Edge Tones - Bamberger, Andreas; Bänsch, Eberhard; Siebert, Kunibert G. (ZAMM - Zeitschrift für angewandte Mathematik und Mechanik, 2004)
We study both, by experimental and numerical means the fluid dynamical phenomenon of edge tones. Of particular interest is the verification of scaling laws relating the frequency f to given quantities, namely d, the height of the jet, w, the stand-off distance and the velocity of the jet. We conclude that the Strouhal number Sd is related to the geometrical quantities through Sd = C · (d/w)n with n ≈ 1, in contrast to some analytical treatments of the problem. The constant C of the experiment agrees within 13-15% with the result of the numerical treatment. Only a weak dependence on the Reynolds number with respect to d is observed. In general, a very good agreement of the experimental and the numerical simulations is found. © 2004 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
UnivIS-Import:2015-03-09:Pub.2004.nat.dma.lama3.experi
Keywords: Adaptive finite elements; Edge tones; Experimental investigation; Navier-stokes equations; Numerical methods